Digital Assets: The Idea of Indonesian Property Law Reform and Its Potential as a Collateral Object - Asmara, Teguh Tresna Puja; Abubakar, Lastuti; Handayani, Tri (Hasanuddin Law Review, 2019)
Digital assets in the broadest sense can be interpreted to cover all electronic assets including social media accounts. Nowadays, besides being used to interaction, social media accounts can also be utilized to gain income or material benefits. In addition, social media accounts are generally handled by influencers with abundant followers. One of the social media used by influencers on the internet is YouTube. The social media actors on YouTube are referred to as YouTubers or content creators. This research is a normative juridical legal research with the descriptive method of analysis. The result of the study shows that YouTube accounts as digital assets in practice can be used as assets in business activities. This is proven by the existence of a YouTuber or content creator who sells his account for charity or commercial purposes. In the future, YouTube accounts can potentially be a digital asset that can be used as a collateral object due to its economic value. Nevertheless, based on the property of law in Indonesia, YouTube social media accounts as a digital asset cannot be qualified as an asset yet, therefore a redefinition, a reconceptualization and a reform of the property of law are considered necessary.